Dipolar ordering in a molecular nanomagnet detected using muon spin relaxation - Pratt, F; Micotti, E; Carretta, P; Lascialfari, A; Arosio, P; Lancaster, T; Blundell, S; Powell, A (American Physical Society, 2014)
Implanted muons have been used as a local probe to detect the magnetic ordering in the molecular magnetic nanodisk system Fe19. Two distinct groups of muon sites are identified from the relaxation data, reflecting sites near the magnetic core and sites distributed over the rest of the molecule. Dipole field calculations and Monte Carlo simulations confirm that the observed transition in Fe19 is consistent with magnetic ordering driven by interactions between molecules that are predominantly dipolar in nature. The triclinic crystal structure of this system gives the dipolar field a significant component transverse to the easy spin axis and the parallel component provides a dipolar bias closely tuned to the first level crossing of the system. These factors enhance the quantum tunneling between levels, thus enabling the system to avoid spin freezing at low temperatures and efficiently reach the dipolar ordered state. © Published by the American Physical Society.